Picosecond Photovoltaic Response in Tilted Lanthanum Doped Manganite Films - Zhiqing Lu; Hao Ni; Jianfeng Xi; Xiaoming Li; Kun Zhao (International Journal of Photoenergy)
Anisotropic picosecond photovoltaic responses were observed in lanthanum doped manganite LaxCa1-xMnO3 (x=0.67 and 0.4) thin films, which were deposited on miscut LaSrAlO4 substrates under ultraviolet pulsed laser irradiation without external bias. The 10%–90% rise time and the full width at half maximum of La0.67Ca0.33MnO3 were 470 and 585 ps, respectively, and those of La0.4Ca0.6MnO3 were 220 and 515 ps. The photovoltage sensitivities of La0.67Ca0.33MnO3 and La0.4Ca0.6MnO3, which are sensitive to the concentrations of lanthanum of the samples, are 0.28 V/mJ and 3.47 V/mJ, respectively. The photosensitivity in the films deposited on MgO is higher than that in those deposited on LaSrAlO4 substrates, for it has a big lattice mismatch. These results should open a route for the application of lanthanum doped manganite as an ultrafast photodetector material.